Suitability Studies of different Milk Proteins for Supplementation in Functional Extruded Snack - Yadav, Upasana; Singh, R. R. B.; Prakash, Karnika; Arora, Shalini; Chatterjee, Alok (Indian Journal of Dairy Science, 2020)
Carbohydrate based snacks clubbed with frying have substantial dominance on the Indian snack market, depriving nutrition. But awareness for alternative healthier snacks has already attracted market attention. In the present study, an effort was ventured by utilizing the combined benefits of high carotene sweet potato flour, barley flour, rice flour and milk protein (Whey Protein Concentrate (WPC)-70/ Skim Milk Powder (SMP)/ rennet casein) to design a low fat-high protein, crisp snack by extrusion cooking. The conditions employed for snack processing were the temperature of heater 1 (110Â°C) and 2 (40Â°C), screw speed (370 rpm), and die diameter (4 mm). The effect of different proteins and their levels on snack quality was evaluated by physical and sensory responses like hardness (N), L*, a*, and b* color values, expansion index (EI) and sensory scores (color and appearance, flavor, texture and overall acceptability). The results revealed that the addition of SMP at different rates did not show significant (p>0.05) effect on expansion index, color & appearance, and flavor score of the snack. Whereas incorporating rennet casein as a source of quality protein, EI increased significantly (p<0.05) at 15% and there was a significant effect on the sensory parameters with increasing rennet level. However, increasing WPC-70 addition, the EI and sensory scores declined, and the hardness of the snack increased. Highest EI (3.18) and sensory scores were observed at 15% level of casein. From quantified parameters, casein was deduced to be most acceptable milk protein source for the intended snack.